Kajian Non-muslim Terhadap Islam Kajian Semantik Toshihiko Izutsu Terhadap Al-Quran - Muhsinin, Mahmud (Fakultas Agama Islam, 2016)
In view of Toshihiko Izutsu, the Arabs do not like the Greeks who likes to philosophize and think global. Pre-Islamic Arab nation is a nation of pragmatists, fatalist, and particularist, who prefer to reveal the details rather than global. Izutsu give a neat illustration, if an Arab find a tree, then he is happy to tell as much detail as possible branches, leaves much detail as possible, or the beauty of the flowers with a variety of expressions. Perhaps this is the reason why the Arabic language is rich with the term for an object that looked the same. However, on the other hand, they tend to not see the tree as a system.The arrival of the Koran in the middle of the Arabs led to words and specific terminology previously unconnected become closely intertwined and form a system and a new world view, which departed from the concept of God. As the word